Mapping Trends and Hotspots Regarding Clinical Research on COVID-19: A Bibliometric Analysis of Global Research - Xia, Demeng; Yao, Renqi; Wang, Sheng; Chen, Gaoqi; Wang, Yin (Frontiers in Public Health, 2021)
Purpose Outbreak in December 2019 and has not been completely controlled, COVID-19 has received a lot of attention from countries around the world. Many related clinical researches including clinical trials have been published, but until now, there has been no bibliometric analysis of these publications. Methods The global publications on COVID-19 from January 2020 to December 2020 were extracted from Web of Science collection database. VOSviewer software and CiteSpace were employed to perform the bibliometric study. Finally, we obtained information about relevant clinical randomized controlled trials (http://clinicaltrials.gov.com/). Results China published the most publications in this field and had the most citations as well as H-index. The Journal of medical virology published the most papers related to the COVID-19 in terms of journals. Huazhong University of Science and Technology have most publications in terms of institutions and research by Wang, JW received the highest number of citations in terms of authors. Conclusion The diagnosis, prevention and prognosis of COVID-19 are still the focus of our attention at present. The overall analysis of the disease from the perspective of epidemiology and statistics were identified as the emerging topics. However, finding an effective treatment remains the focus of clinical trials.